2021
DOI: 10.1016/j.jsps.2021.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Design Your Exam (DYE): A novel active learning technique to increase pharmacy student engagement in the learning process

Abstract: Background Due to the COVID-19 pandemic, innovative e-learning solutions should be implemented to deliver knowledge to health care students remotely. Presently, there is a paucity of studies in the literature that have examined student-designed assessments in the classroom. Objectives To examine the educational outcomes comparing Design Your Exam (DYE) activity versus instructor-designed end-of-class (EOC) quizzes and explore student perceptions and preferences for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The post-tests were very useful in helping students to understand the most important information and motivating them to focus during the lecture ( Table 3 ). Similarly, several previous studies showed positive educational outcomes of “End of class” (post-lecture) tests in significantly increasing average exam scores [ 48 ], encouraging student introspection related to their personal comprehension [ 49 , 50 ], as well as improvements in student course satisfaction [ 51 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The post-tests were very useful in helping students to understand the most important information and motivating them to focus during the lecture ( Table 3 ). Similarly, several previous studies showed positive educational outcomes of “End of class” (post-lecture) tests in significantly increasing average exam scores [ 48 ], encouraging student introspection related to their personal comprehension [ 49 , 50 ], as well as improvements in student course satisfaction [ 51 ].…”
Section: Discussionmentioning
confidence: 71%
“…The high percentage and similarities in student attendance and scores are indications that both PICkLE and iFEEL activities are non-inferior to each other and can be an alternative to the standard didactic lectures as a part of either live or distant learning courses. A recent study also concluded that a non-significant increase in student exam scores when comparing two different active learning activities is a positive indication that both strategies are equally effective in enhancing student learning and understanding as an alternative to traditional lectures [ 50 ]. Moreover, mean post-test scores were non-significantly higher in the iFEEL activity compared to pre-pandemic live PICkLE.…”
Section: Discussionmentioning
confidence: 99%
“…The surveys were designed using Google Forms ® and the survey link was sent by email to students [27]. Two reminders were subsequently sent to the students to encourage their participation.…”
Section: Questionnaires To Evaluate Student's Perceptions Of Srsmentioning
confidence: 99%
“…All surveys were created using Google Forms ® and the survey links were sent by email to the faculty member so that he/she completes the faculty survey and forward the students survey to his students encouraging them to complete it [5].…”
Section: Questionnaires To Evaluate Student's and Faculty's Perceptionsmentioning
confidence: 99%
“…With the advancement of technology and its availability, it has become necessary to use it to solve problems related to education, particularly the introduction of an interactive classroom in which the student is the main focus and is given the time and opportunity to participate and interact with the scientific material presented. The continuous development of modern teaching methods, by teachers, is vital to enhance learning, including the involvement of students in the educational process and the use of modern and more effective teaching techniques during lectures [5,6].…”
Section: Introductionmentioning
confidence: 99%